Homeopathic Medical Education: Ensuring Quality Standards Globally (Homoeopathy for All, 2021)
World Health Organization (WHO) considers ‘Homeopathy’as the second most popular and frequently used form of Traditional and Complementary Medicine (T&CM) that is widely used in all WHO regions with a presence over 80 countries worldwide. With a legal recognition as an individual system of medicine in 42 countries, it is recognized as a part of complementary and alternative medicine in 28 countries.1
Keywords: WHO European Region; WHO African Region